Dual‐Quasi Bound States in the Continuum Enabled Plasmonic Metasurfaces. Issue 19 (8th July 2022) - Zhou, Yi; Guo, Zhihe; Zhao, Xuyang; Wang, Feilong; Yu, Zhiyuan; Chen, Yizhen; Liu, Zhiran; Zhang, Shuyu; Sun, Shulin; Wu, Xiang
Abstract: Localized surface plasmon resonances (LSPRs) in metallic nanostructures attract great attention for their potential applications such as highly sensitive optical sensors. However, the performance of LSPR sensors is strongly hampered by their low quality ( Q ) factors due to the intrinsic ohmic losses and far‐field radiation losses. Here, a kind of all‐metal metasurfaces that can achieve high‐ Q and high figure of merit (FOM) resonances based on bound states in the continuum (BICs), is theoretically designed and experimentally demonstrated. The devices can simultaneously exhibit symmetry‐protected and Friedrich–Wintgen quasi‐BICs features at normal incidence, leading to higher Q ‐factors than those solely inspired by single quasi‐BIC. Additionally, the constraint of symmetrical dielectric environment for common metasurfaces can be released by utilizing a metal substrate rather than a dielectric one. The proof‐of‐concept experiments demonstrate the high performances of such dual quasi‐BIC based plasmonic refractive index sensors with the Q ‐factor of 145, the sensitivity of 657 nm RIU ‐1, and the FOM of 109 RIU ‐1 . These findings may stimulate some promising applications, such as biosensing, optical lasing, and light absorption. Abstract : A kind of reflective plasmonic dual‐quasi bound state in the continuum (BIC) metasurfaces is theoretically designed and experimentally demonstrated. Excitations of both symmetry‐protected and Friedrich‐Wintgen quasi‐BIC modes gaurantee the high quality ( Q ) factor resonance of our device. Proof‐of‐concept experiments demonstrate the high‐performance and robust sensing platform with the Q ‐factor of 145 and the figure of merit of 109 RIU −1 .